Modelos de comportamento de busca de informação: contribuições para a organização da informação - Garcia, Rodrigo Moreira [UNESP] (2007)
With the development of the Web and, consequently, of the digital libraries, open archives, repositories between other, new systems and information sources have been created, placing the users in a new search and information retrieval environment, characterized by the abundance of informational resources disposed in the hypertext format, increasing the access possibilities significantly. Ahead of this information digital environment, one of the Indexing Languages functions is to represent the information of the documents contained in these information systems, so that the user be capable to access that information for the use, communication and, mainly, for the generation of new knowledge. However, the problem-key of the Information Retrieval goes by the search of theoretical and methodological proceedings for the Information Organization and Representation. In other words, the principal problematic is to find means of improving the methods of Information Organization at the conceptual level, in way to increase the accessibility for the end-users. Ahead this, an exploratory study of theoretical analysis was proposed of some information search behavior models that, in agreement with the specialized literature, they are the ones that have larger impact in research terms in the area. Such models can be incorporate to the information thematic treatment processes, allowing to librarians and indexers the if give bill of the intervening variables in the search and information retrieval process of the users and, this way, that they understand the factors that affect the information organization and representation. As results are considered that an approach that tries to place the user in the center of the concerns in the Information Organization should appeal to the accumulated experience in the calls studies of users. It is ended that the studies about the users' information behaviors... (Complete abstract click electronic access below)